I am trying to use substitution on this indefinite integral. Here is what I have so far: let u = -cosx du/dx = sinx du = sinx dx - so I am left with: sub back in Where am I going wrong? Angus
Follow Math Help Forum on Facebook and Google+
what you want to integrate is But you are integrating
Originally Posted by angypangy I am trying to use substitution on this indefinite integral. Here is what I have so far: Or did you mean as issacnewton suggests? let u = -cosx du/dx = sinx du = sinx dx - so I am left with: sub back in Where am I going wrong? Angus
Originally Posted by issacnewton what you want to integrate is But you are integrating Thanks Isaac I was revising and read up on substitution assuming I would need to substitute. But of course you are correct. Thanks.
View Tag Cloud